2017
DOI: 10.1002/2211-5463.12349
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of strand‐specific miRNA‐101‐3p and miRNA‐101‐5p for hepatocellular carcinoma and a bioinformatic analysis of their possible mechanism of action

Abstract: There is accumulating evidence that miRNA might serve as potential diagnostic and prognostic markers for various types of cancer. Hepatocellular carcinoma (HCC) is the most common type of malignant lesion but the significance of miRNAs in HCC remains largely unknown. The present study aimed to establish the diagnostic value of miR‐101‐3p/5p in HCC and then further investigate the prospective molecular mechanism via a bioinformatic analysis. First, the miR‐101 expression profiles and parallel clinical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Among two mature miRNAs, miR-101-3p is generated from the 3′-ends of the precursor, and miR-101-5p is generated from the 5′-end of pre-miR-101 34. Accumulating evidence have demonstrated that the levels of miR-101-5p are decreased in many malignances, including liver cancer 35. In NSCLC, miR-101-3p suppresses the growth and metastasis of cancer cells via blocking the phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) signaling pathway and regulating the expression of metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1) 14.…”
Section: Discussionmentioning
confidence: 99%
“…Among two mature miRNAs, miR-101-3p is generated from the 3′-ends of the precursor, and miR-101-5p is generated from the 5′-end of pre-miR-101 34. Accumulating evidence have demonstrated that the levels of miR-101-5p are decreased in many malignances, including liver cancer 35. In NSCLC, miR-101-3p suppresses the growth and metastasis of cancer cells via blocking the phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) signaling pathway and regulating the expression of metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1) 14.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small, non-coding RNA molecules of ~ 22 nucleotides, which perform functions in the post-transcriptional regulation of gene expression ( 11 15 ). miRNAs act as oncogenes or antioncogenes in tumorigenesis, thus influencing the onset and development of tumors ( 16 – 20 ). Previous studies have shown that the downregulated expression of miRNA may be essential in the onset and development of PCa ( 21 – 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Where SE represents sensitivity; SP represents specificity; TP+FN is the sample size of the tumour; and FP+TN is the sample size of the normal control. The meta-analysis was performed using STATA 12.0 (StataCorp LP, College Station, TX, USA) for pooling the standardized mean difference (SMD), sensitivity, specificity and summary ROC of HOXA11 expression ( 16 , 17 ). An I 2 test was used to evaluate heterogeneity, when I 2 <50%, a fixed-effects model was used; while I 2 ≥50% the random-effects model was selected ( 18 ).…”
Section: Methodsmentioning
confidence: 99%